2016
DOI: 10.3844/ajassp.2016.408.419
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Factors used by Farmers to Manage Risk. A Case Study on Italian Farms

Abstract: The study analyses the strategies Italian farmers use to cope with the risks that face their production. We develop cross-sectional and longitudinal analyses as well as analyses of correlation that underline the main differences between the way farms adapt their structure and management towards risk. The expected output is an analysis of farms' approach to risk management in relation to the risk exposure. The present study is the result of research conducted by INEA "Research and technical support on natural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…(), a better understanding of informational asymmetries in crop insurance, which include adverse selection, moral hazard and advantageous selection behaviours, is a necessary first step to introduce public interventions aimed at increasing participation in the programme. Furthermore, insights from studies that look at these behaviours could help in development of integrated policy schemes that combine crop insurance with other risk‐mitigating mechanisms (like programmes to encourage adoption of good agricultural practices), which in turn can help reduce overall farm risk exposure (See Pontrandolfi et al ., ).…”
mentioning
confidence: 97%
“…(), a better understanding of informational asymmetries in crop insurance, which include adverse selection, moral hazard and advantageous selection behaviours, is a necessary first step to introduce public interventions aimed at increasing participation in the programme. Furthermore, insights from studies that look at these behaviours could help in development of integrated policy schemes that combine crop insurance with other risk‐mitigating mechanisms (like programmes to encourage adoption of good agricultural practices), which in turn can help reduce overall farm risk exposure (See Pontrandolfi et al ., ).…”
mentioning
confidence: 97%
“…irrigation), the share of owned land, the level of feed self-sufficiency, the quality of feed diet and livestock productivity. Irrigation, pesticides and fertilisers (Pontrandolfi et al , 2016) represented some major examples of self-covering strategies. Enjolras et al (2014) and Trestini, Pomarici and Giampietri (2017) found that input intensification is associated with more risky production.…”
Section: Methodsmentioning
confidence: 99%
“…Building the agricultural sector's resilience to drought, then, requires effective short-term hazard management improvements, but also investments that will improve the sector's capacity to manage or adapt to these types of events in the long-term. Amongst other challenges, the government must find the most effective balance between investing in preparedness and prevention versus hazard response; more effectively manage water resources amongst competing uses; and incentivise improved farm-level capacity 2 The degree to which this is the case depends on whether farmgate prices increase versus wholesale or retail prices, as the value of an increase only in wholesale or retail prices will largely be captured elsewhere in the value chain. to manage drought and adapt to changing conditions.…”
Section: Figure 1 Frequency Of Disaster Events In Italy 2000-2020mentioning
confidence: 99%
“…This case study examines how governance arrangements and policy measures help to build the resilience of Italy's farmers and agricultural sector to natural hazard-induced disasters (NHID). It is one of seven case studies 1 prepared for the joint OECD-FAO project on Building Agricultural Resilience to Natural Hazard-Induced Disasters: Insights from Country Case Studies (OECD-FAO, 2021 [2]). This project examines Disaster Risk Management (DRM) frameworks in selected OECD and developing countries to identify what governments and agricultural sector stakeholders can do to build resilience to NHIDdefined here as the ability of farmers to prepare and plan for, absorb, respond, recover from, and more successfully adapt and transform in response to natural hazards (OECD, 2020 [3]).…”
Section: Introductionmentioning
confidence: 99%